Laryngeal rhabdomyosarcoma in a dog: Case report - Dias, F. G.G.; Cintra, P. P.; Calazans, S. G.; Jorge, A. T.; Pereira, L. F.; Dias, L. G.G.G. [UNESP]; Olivio, M. B.; Magalhães, G. M. (FapUNIFESP (SciELO), 2018)
The larynx is part of the upper respiratory tract and is responsible for phonation. It allows air to pass between the pharynx and the trachea, but prevents food from entering the airways. Laryngeal neoplasms, including rhabdomyosarcomas, are uncommon in dogs. However, these tumors can trigger numerous progressive clinical signs related to respiratory difficulty and altered phonation. The diagnosis of laryngeal cancer should be made based on the history and symptoms of the patient, combined with complementary tests. The treatment of choice is surgical excision, combined or not with chemotherapy. In view of the low incidence of laryngeal cancer, the objective of the present work was to describe a case of laryngeal rhabdomyosarcoma detected during necropsy of an adult dog and diagnosed by histopathology, in addition to raising awareness about the importance of the diagnosis and early therapy for the quality of life and survival of affected patients. The results showed that the location of the tumor impaired its early diagnosis. Although malignant, the animal did not develop metastases as has been described in the literature.

A laringe é um dos órgãos que compõem o trato respiratório superior, sendo também responsável pela fonação. Permite a passagem do ar entre a faringe e traqueia, mas impede que alimentos adentrem as vias aéreas. As neoplasias laringeanas, incluindo os rabdomiossarcomas, são incomuns em cães, porém, quando presentes, desencadeiam inúmeros sinais clínicos progressivos relacionados à dificuldade respiratória e à alteração na fonação. O diagnóstico das neoplasias na laringe deve ser baseado no histórico e na sintomatologia do paciente, associado a exames complementares. O tratamento de eleição é a exérese cirúrgica, concomitante ou não com a quimioterapia. Desse modo, diante da baixa incidência desse tipo neoplásico, inclusive na laringe, o objetivo do atual trabalho é descrever o caso de rabdomiossarcoma em laringe, detectado durante o exame de necropsia de um cão adulto e diagnosticado por histopatologia, bem como conscientizar sobre a importância do diagnóstico e da terapêutica precoce na qualidade de vida e sobrevida dos afetados. De acordo com a descrição do caso, pode-se admitir que a localização da neoplasia prejudicou o diagnóstico precoce e que, apesar de esta ser maligna, não houve metástases conforme descrição na literatura.
Keywords: Oncologia; Oncology; Pequenos animais; Rabdomiossarcoma; Respiratory system; Rhabdomyosarcoma; Sistema respiratório; Small animals